2013
DOI: 10.1002/mcda.1491
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Optimization for the Asset Allocation of European Nonlife Insurance Companies

Abstract: An optimal asset allocation is crucial for non-life insurance companies. The most previous studies focused on this topic use a mono-objective technique optimization. This technique usually allows the maximization of shareholders' expected utility. As non-life insurance company is a complex system, it has many stakeholders other than shareholders. So, the satisfaction of the shareholders' expected utility cannot lead usually to the satisfaction of other stakeholders' objectives. Therefore, the focus on utility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Following Färe et al (2005), Park and Weber (2006) and Jarraya and Bouri (2013), we adopt a quadratic functional form in the direction of parameterizing the directional output distance function (See Appendix).…”
Section: Modelmentioning
confidence: 99%
“…Following Färe et al (2005), Park and Weber (2006) and Jarraya and Bouri (2013), we adopt a quadratic functional form in the direction of parameterizing the directional output distance function (See Appendix).…”
Section: Modelmentioning
confidence: 99%
“…They concluded that the evolutionary algorithms are excellent options to find good solutions in short computation times. A multi-objective framework for EU-based non-life insurance companies is developed in [26] in order to find the best asset allocation that maximizes simultaneously expected utility and technical efficiency. In this manner, it is possible to consider both shareholders', as well as customers' objectives.…”
Section: Introductionmentioning
confidence: 99%